Properties of bcr-abl-transformed mouse 12B1 cells secreting interleukin-2 and granulocyte-macrophage colony-stimulating factor: I. Derivation, genetic stability, oncogenicity and immunogenicity - Petráčková, Martina; Tachezy, Ruth; Vonka, Vladimír (International journal of oncology, 2012)
The highly oncogenic bcr-abl-transformed mouse (Balb/c) 12B1 cells were transfected with plasmids carrying genes for either mouse interleukin-2 (IL‑2) or the mouse granulocyte-macrophage colony-stimulating factor (GM‑CSF) and the gene for blasticidine resistance. From the transduced cells several clones widely differing in the production of either cytokine were isolated. For further experiments, clones with the highest secretion of the cytokines were selected. When administered subcutaneously to mice, the IL-2-secreting cell line was approximately hundred times less pathogenic than the parental cells. A portion of animals developed small, spontaneously regressing tumours and most of them became resistant to challenge with the parental cells. Cell populations from either solid tumours or from organs infiltrated by the tumour cells predominantly consisted of cells which did not produce IL-2 and had lost resistance to blasticidine. This indicated that the IL-2 secreting cells were genetically unstable in the course of their propagation in vivo. On the other hand, the GM‑CSF‑secreting cells were more pathogenic than the parental cells, induced extensive organ damage and remained genetically stable in the course of their growth in vivo. The pathogenicity of different GM‑CSF secreting clones directly depended on the magnitude of production of this cytokine. When used in the form of inactivated vaccines, the GM-CSF-secreting cells were more immunogenic than the IL-2-secreting cells. In comparative experiments, similar results were obtained with GM‑CSF- and IL-2-secreting cells derived from B210 cells, another bcr-abl transformed cell line.
Keywords: Animals; Drug Resistance, Neoplasm; tumor burden; Female; Cell Line, Tumor; Blotting, Western; ženské pohlaví; interleukin-2; transfekce; bcr-abl fúzní proteiny; časové faktory; Cancer Vaccines; Cell Line, Transformed; Time Factors; lidé; Transfection; Tumor Burden; Mice; transplantace nádorů; Interleukin-2; chemorezistence; Mice, Inbred BALB C; myši; regulace genové exprese u leukemie; protinádorové vakcíny; western blotting; Granulocyte-Macrophage Colony-Stimulating Factor; myši inbrední BALB C; leukemie; transdukce genetická; Transduction, Genetic; Gene Expression Regulation, Leukemic; Leukemia; Neoplasm Transplantation; zvířata; Fusion Proteins, bcr-abl; transformované buněčné linie; nádorové buněčné linie; faktor stimulující granulocyto-makrofágové kolonie; Humans